DEVELOPMENT OF GAMIFICATION-BASED DIGITAL FLIPBOOK MEDIA ON IPAS MATERIAL (STUDY ON GRADE IV ELEMENTARY SCHOOL) - Bayat, Palgunadi Abdulah; Nusantara, Toto; Suciptaningsih, Oktaviani Adhi (PT. BATARI EDU CALYA, 2023)
The purpose of this research and development is to produce media products that are valid, complete, practical, and attractive. This research was tested at SD Negeri Balearjosari 1 guided by the ADDIE model to develop digital flipbook media. The data collection techniques used to develop batumema multimedia are tests, observation, documentation, interviews, and questionnaires. The results of this study are in the form of digital flipbook media by utilizing technological developments based on gamification, the media developed can be said to be valid, complete, practical, and interesting, this is evident from the results of data analysis, namely (1) the results of media validation with a total score of 49 with a percentage calculation obtaining 87.5% including the criteria